Alcohol Consumption Moderated the Association Between Levels of High Blood Lead or Total Urinary Arsenic and Bone Loss - Hsueh, Yu-Mei; Huang, Ya-Li; Chen, Hsi-Hsien; Shiue, Horng-Sheng; Lin, Ying-Chin; Hsieh, Ru-Lan (Frontiers in Endocrinology, 2021)
Metal exposure and lifestyle are important risk factors for osteoporosis. Our study aimed to investigate the association between red blood cell lead and cadmium, total urinary arsenic, and plasma selenium levels and bone mineral density (BMD). In addition, we explored whether alcohol and coffee consumption modified the association between BMD and metals and metalloids. In total, 437 participants who underwent adult or senile physical examinations were recruited. Bone loss was defined as a calcaneus BMD T-score of <-1. Blood cadmium and lead and plasma selenium levels were measured using inductively coupled plasma mass spectrometry. Levels of urinary arsenic species were determined using high-performance liquid chromatography–hydride generator–atomic absorption spectrometry. The total urinary arsenic level was defined as the sum of the levels of urinary arsenic species. The BMD T-scores decreased significantly with increasing blood lead levels. The BMD T-scores also showed a downward trend with increasing total urinary arsenic levels. The odds ratio (OR) and 95% confidence interval (CI) for bone loss in patients with blood lead levels >57.58 versus 35.74 g/dL were 1.98 and 1.17–3.34. In addition, the greater the lead or arsenic exposure and alcohol intake were the higher the OR for bone loss with multivariate ORs of 2.57 (95% CI 1.45–4.56) and 2.96 (95% CI 1.67–5.22), respectively. To the best of our knowledge, this study is the first to demonstrate that high total urinary arsenic or blood lead levels and frequent or occasional alcohol consumption had a significant multiplicative interaction for increasing the OR for bone loss.